Settlement of the Fergana region by peasants-migrants in the late XIX – early XX centuries (Journal of history, 2021)
The relevance of the study is due to the fact that the problem of the settlement of southern Kyr- gyzstan in the late XIX – early. XX centuries remains insufficiently studied. The purpose of this work is to reveal the history of the settlement of the Fergana region by migrants based on the introduction into scientific circulation of materials from Russian archives and pre-revolutionary authors. The content of the article is based on the application of the principles of historicism and objectivity. The stages of the resettlement of peasants and the formation of resettlement settlements in the Kyrgyz volosts of the Fergana region are highlighted. Established in 1906, the Resettlement Administration was engaged in the creation of a resettlement fund for the settlement of settlers through the seizure of Kyrgyz lands in the foothill and mountainous regions. Russian peasants were allocated land not by the number of family members, but by household – 10 acres of land per allotment, including arable land, hayfields, pasture and manor land. Despite the fact that 40% of the region’s agricultural areas were occupied by cotton sowing, the administration was actively working to create Russian settlements. The scale of the resettle- ment of peasants to the southern regions of Kyrgyzstan was such that if by 1902. In the Fergana region, only 7 Russian settlements were created, then by 1916 68 resettlement settlements were created.Key words: Fergana region, immigrants, land issue, Kyrgyz, agriculture, cotton growing, Andijanuprising.